Ambidextrous leadership: a narrative literature review for theory development and directions for future research. Issue 2 (3rd December 2021) - Kafetzopoulos, Dimitrios
Abstract : Purpose: This study seeks to provide a narrative literature review of existing empirical research, in order to better understand the processes and theory of ambidextrous leadership, as well as its influence on followers, employees and organizations. Design/methodology/approach: Data from 26 studies were extracted and synthesied providing a critical discussion about the methodological and theoretical aspects of the studies identified in the review. Findings: It was revealed the attributes for an effective ambidextrous leader, it was presented the recently proposed concept of ambidextrous leadership theory and it was noticed the main criticisms against the findings of the extant ambidextrous leadership literature. It was also identified many research gaps in the literature which in turn can guide academics in the development of ambidextrous leadership. Research limitations/implications: The ambidextrous leadership theory represents a novel and unique approach to the domain of leadership for creativity and innovation. It is shared across hierarchical levels throughout the organization. Leaders have a significant effect on employees' behaviors and should determine its applicability to different situations. Organizations require ambidextrous managers who combine flexible, situational and versatile leadership styles developing ever increasingly new and divergent ideas. Many research gaps in the literature were also identified that can guide academics in the development of ambidextrous leadership. Practical implications: Understanding that ambidextrous leadership is required to significantly influence ambidexterity and innovation allows organizations to direct their leadership selection and development. Originality/value: This review contributes to the ambidextrous leadership literature by creating a holistic picture of where it has been and where it should go.